2014
DOI: 10.1371/journal.pone.0100542
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Pathogenic Properties of Klebsiella oxytoca Isolated from Laboratory Animals

Abstract: Klebsiella oxytoca is an opportunistic pathogen implicated in various clinical diseases in animals and humans. Studies suggest that in humans K. oxytoca exerts its pathogenicity in part through a cytotoxin. However, cytotoxin production in animal isolates of K. oxytoca and its pathogenic properties have not been characterized. Furthermore, neither the identity of the toxin nor a complete repertoire of genes involved in K. oxytoca pathogenesis have been fully elucidated. Here, we showed that several animal isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 50 publications
1
37
0
2
Order By: Relevance
“…Klebsiella oxytoca is a gram-negative bacterium belonging to the Enterobacteriacae family. It is considered an opportunistic pathogen [20]. Polymicrobial endocarditis, as found in our case, occurs mainly in IVDAs [21] and is associated with an especially high mortality rate [17].…”
Section: Page 8 Of 19supporting
confidence: 50%
“…Klebsiella oxytoca is a gram-negative bacterium belonging to the Enterobacteriacae family. It is considered an opportunistic pathogen [20]. Polymicrobial endocarditis, as found in our case, occurs mainly in IVDAs [21] and is associated with an especially high mortality rate [17].…”
Section: Page 8 Of 19supporting
confidence: 50%
“…For example, Klebsiella- mediated, antibiotic-associated hemorrhagic colitis has been linked to the NRP tilivalline (22) . 224, 225 Tilivalline was first isolated from Klebsiella oxytoca in the early 1980s and was shown to have toxicity against mouse leukemia L1210 cells. 226, 227 More recently, the pathological symptoms of tilivalline-mediated damage in the colon were more pronounced in animals treated with antibiotics and infected with K. oxytoca as compared to control animals.…”
Section: Natural Products In Human Diseasementioning
confidence: 99%
“…Tilivalline has been shown to induce caspase-3-dependent apoptosis in cultured human epithelial cells, which has also been observed in the pathology of antibiotic-associated hemorrhagic colitis. 224, 225 …”
Section: Natural Products In Human Diseasementioning
confidence: 99%
“…KPC-producing K. oxytoca isolates are rarely reported [18]. K. oxytoca is an opportunistic pathogen and is now identified and introduced as an important clinical pathogen that is associated with nosocomial infections in hospitalized patients, including children, newborns, and individuals with immune deficiency [19]. A few studies have reported the identification of the KPC gene in K. oxytoca strains in some countries such as Austria [18], Brazil [20], and Venezuela [21].…”
Section: Introductionmentioning
confidence: 99%